Synthesis of Educational Management System for Children with Learning Disabilities in Basic Education - Pisapak, Jittima; Sangjun, Wiparat; Pilanthananond, Nataya (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The study adopted a documentary research approach. The aims of this study were 1. to compare educational management systems for children with Learning Disabilities at the basic education level in foreign countries with Thailand, and 2.to create and assess the quality of a model of the educational management system for children with Learning Disabilities at the basic education level in Thailand. The research instrument was a quality assessment form on the appropriate education management system. The sample consisted of 1. the 7 purposive sampling countries used in this study, and 2. the 12 experts who assessed the quality of management model and were selected based on purposive sampling. Study period 2015 - 2021. The mean and standard deviation were used to analyze data. The findings indicate that 1. most countries used in this study, including Thailand, do not have specific laws for children with Learning Disabilities. The learning standards used for children with Learning Disabilities are the same as for normal children. The agency in charge is a national agency which has different management approaches; that is, the model for the educational service area adopting the direct policy from the central unit and the model for the central unit passing the authority to the educational service area to operate by itself. 2. the developed management model for children with Learning Disabilities in Thailand included 2 main issues: 1. Determination of educational management policies and 2. Determination of learning standards for children with Learning Disabilities. The experts assessed the overall quality of the educational management model and extremely agreed on 2 issues; that is, there should be specific laws for children with Learning Disabilities under operation of the Bureau of Special Education Administration serving as the main agency adopting the major policy from the central unit and passing the authority to the level of the educational service area for implementation at the school level and the specific learning standards for children with Learning Disabilities should be determined along with the learning standards for normal children.